Endophytes for a Growing World 2019
DOI: 10.1017/9781108607667.006
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Methods for Biological Control of Barley Diseases Including the Role of Endophytes

Abstract: Barley is an important crop worldwide with production largely used for animal feed and alcoholic beverages. Diseases are a major limiting factor to its production. Th ese have, up until recently, been controlled by agrochemicals. However, legislation on the use of agrochemicals, especially within the European Union, is being tightened and there is growing interest in integrated pest management . Th is means that there is an increasing focus on controlling diseases using biological control . Living microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…Only a limited number of studies have investigated the control of barley diseases using endophytes [ 2 ]. If the endophytic lifestyle of the biocontrol agent is the reason for the reduction of disease symptoms, then it is relevant to examine the colonisation of the isolate and certainly if the endophyte has been isolated from a different species than the crop [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a limited number of studies have investigated the control of barley diseases using endophytes [ 2 ]. If the endophytic lifestyle of the biocontrol agent is the reason for the reduction of disease symptoms, then it is relevant to examine the colonisation of the isolate and certainly if the endophyte has been isolated from a different species than the crop [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barley is the fourth most produced cereal crop in the world [ 1 ] and barley diseases result in great yield losses [ 2 ]. Some of the most important diseases in Northern Europe include leaf blotch caused by Rhynchosporium graminicola, Ramularia leaf spot (caused by Ramularia collo-cygni ), Fusarium head blight (FHB, caused by Fusarium spp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other important aspects of endophyte effects on plants relate to nutrient uptake and use, and biocontrol activity (Murphy et al 2014;Høyer et al 2019). Yakti et al (2018) have shown that two model Dark Septate Endophytes (DSE) improved nitrogen uptake in tomato from organic sources and suggested that this might be due to nutrient mobilisation rather than hyphal transport to the plant.…”
Section: Ecologymentioning
confidence: 99%
“…Recent studies on the study of barley diseases with soil infection were carried out to develop a strategy for protecting barley seedlings from infection caused by Sclerotium rolfsii using soil infested with the antagonist fungi Trichoderma (Faruk, 2019), study the effect hydrothermal stress on the development of soil infections in wheat and barley (Toropova et al, 2018), evaluate the effectiveness of pre-sowing seed treatment against infection caused by Fusarium spp. and Cochliobolus sativus (Sooväli et al, 2017), develop protective measures (Gangwar et al, 2018;Høyer et al, 2019;Singh, 2017), identify the soil-habitat barley mosaic virus (Cadot et al, 2017) and study the antagonistic activity of bacterial species of the Bacillus genus on the B. sorokiniana barley as pathogenic fungi (Harba et al, 2020). Currently, there is no research in Kazakhstan on barley diseases with soil infection.…”
Section: Introductionmentioning
confidence: 99%